Costs of Financing U.S. Federal Debt Under a Gold Standard: 1791-1933 - Jonathan Payne; Bálint Szőke; George Hall; Thomas J Sargent (The Quarterly Journal of Economics, 2025)
Abstract From a new data set, we infer time series of term structures of yields on U.S. federal bonds during the gold standard era from 1791–1933 and use our estimates to reassess historical narratives about how the United States expanded its fiscal capacity. We show that U.S. debt carried a default risk premium until the end of the nineteenth century, when it started being priced as an alternative safe asset to U.K. debt. During the Civil War, investors expected the United States to return to a gold standard so the federal government was able to borrow without facing denomination risk. After the introduction of the National Banking System, the slope of the yield curve switched from down to up and the premium on U.S. debt with maturity less than one year disappeared.